2020
DOI: 10.1038/s41598-019-57085-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of NAMPT deletion in projection neurons on the function and structure of neuromuscular junction (NMJ) in mice

Abstract: Nicotinamide adenine dinucleotide (NAD +) plays a critical role in energy metabolism and bioenergetic homeostasis. Most NAD + in mammalian cells is synthesized via the NAD + salvage pathway, where nicotinamide phosphoribosyltransferase (NAMPT) is the rate-limiting enzyme, converting nicotinamide into nicotinamide mononucleotide (NMN). Using a Thy1-Nampt −/− projection neuron conditional knockout (cKO) mouse, we studied the impact of NAMPT on synaptic vesicle cycling in the neuromuscular junction (NMJ), end-pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…[18][19][20][21][22] Recently, we showed that deletion of NAMPT in the projection neurons using conditional and inducible NAMPT knockout (cKO) mice, i.e., Thy1-YFP-NAMPT À/À cKO mice caused motor neuron degeneration, neuromuscular junction (NMJ) abnormalities, muscle atrophy, body weight loss, paralysis and eventually death. 17,23 Our results indicate that the disruptions of bioenergetics and mitochondrial homeostasis contribute to the phenotype. To further investigate the molecular mechanisms of neuronal death in Thy1-YFP-NAMPT À/À cKO mice, we conducted a combined study of metabolomics and high-throughput RNA sequencing (RNA-Seq) to quantitatively analyze metabolic and transcriptional alterations.…”
Section: Introductionmentioning
confidence: 69%
“…[18][19][20][21][22] Recently, we showed that deletion of NAMPT in the projection neurons using conditional and inducible NAMPT knockout (cKO) mice, i.e., Thy1-YFP-NAMPT À/À cKO mice caused motor neuron degeneration, neuromuscular junction (NMJ) abnormalities, muscle atrophy, body weight loss, paralysis and eventually death. 17,23 Our results indicate that the disruptions of bioenergetics and mitochondrial homeostasis contribute to the phenotype. To further investigate the molecular mechanisms of neuronal death in Thy1-YFP-NAMPT À/À cKO mice, we conducted a combined study of metabolomics and high-throughput RNA sequencing (RNA-Seq) to quantitatively analyze metabolic and transcriptional alterations.…”
Section: Introductionmentioning
confidence: 69%
“…The equilibrium of mitochondrial dynamics and normal mitochondrial morphology are critical for maintaining mitochondrial function [ 38 ]. Mitochondria are dynamic organelles whose morphology is directly linked to the maintenance of their functions, and the disruption of their normal shape is a hallmark of mitochondrial dysfunction [ 39 , 40 ]. Mitochondrial dynamics are regulated by the balance of fission and fusion; imbalances in fission and fusion cause mitochondrial abnormalities that lead to many diseases, including cardiovascular disease [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, NMN (400 mg/kg) treatment lessened disease severity, restored motor function, and extended the life span of Thy1-YFP-Nampt −/− cKO mice. Recently, this same team reported that loss of NAMPT in projection neurons cause detrimental effects on the function and structure of NJM, including impaired synaptic vesicle cycling, morphological changes to the motor endplate, alterations of skeletal muscle contractile responses, and noticeable sarcomere misalignment (Lundt et al, 2020). These detrimental effects were reverse by administration of NMN (400 mg/kg/day) for 14 days.…”
Section: Neuroprotective and Cognitive Functionmentioning
confidence: 99%
“…These detrimental effects were reverse by administration of NMN (400 mg/kg/day) for 14 days. However, NMN treatment did not restore skeletal muscle mitochondria morphology change caused by deletion of Nampt (Lundt et al, 2020). Thus, NMN is a potential therapeutic drug for motor neuron (MN) degenerative diseases, including ALS.…”
Section: Neuroprotective and Cognitive Functionmentioning
confidence: 99%